Insights into the location of type I ECG in patients with Brugada syndrome: Correlation of ECG and cardiovascular magnetic resonance imaging - Veltmann, Christian; Papavassiliu, Theano; Konrad, Torsten; Dösch, Christina; Kuschyk, Jürgen; Streitner, Florian; Haghi, Dariusch; Michaely, Henrik J. M.; Schönberg, Stefan; Borggrefe, Martin; Wolpert, Christian; Schimpf, Rainer (Heart rhythm, 2012)
Background - Brugada syndrome is characterized by ST-segment abnormalities in V1-V3. Electrocardiogram (ECG) leads placed in the 3rd and 2nd intercostal spaces (ICSs) increased the sensitivity for the detection of a type I ECG pattern. The anatomic explanation for this finding is pending. - Objective - The purpose of the study was to correlate the location of the Brugada type I ECG with the anatomic location of the right ventricular outflow tract (RVOT). - Methods - Twenty patients with positive ajmaline challenge and 10 patients with spontaneous Brugada type I ECG performed by using 12 right precordial leads underwent cardiovascular magnetic resonance imaging (CMRI). The craniocaudal and lateral extent of the RVOT and maximal RVOT area were determined. Type I ECG pattern and maximal ST-segment elevation were correlated to extent and maximal RVOT area, respectively. - Results - In all patients, Brugada type I pattern was found in the 3rd ICS in sternal and left-parasternal positions. RVOT extent determined by using CMRI included the 3rd ICS in all patients. Maximal RVOT area was found in 3 patients in the 2nd ICS, in 5 patients in the 4th ICS, and in 22 patients in the 3rd ICS. CMRI predicted type I pattern with a sensitivity of 97.2%, specificity of 91.7%, positive predictive value of 88.6%, and negative predictive value of 98.0%. Maximal RVOT area coincided with maximal ST-segment elevation in 29 of 30 patients. - Conclusion - RVOT localization determined by using CMRI correlates highly with the type I Brugada pattern. Lead positioning according to RVOT location improves the diagnosis of Brugada syndrome.
Available online 23 November 2011
Gesehen am 18.02.2019